The effect of aerobic rehabilitation programs and curcumin supplementation on VO2max and certain cardiovascular risk factors in patients with GABS - H Ghaedi; M Ghahramani; S Behzadi; M Ghahramani (Armaghane Danesh Bimonthly Journal)
Abstract Objective: The aim of the present study was to investigate the effect of an aerobic rehabilitation program and curcumin consumption on VO2max and cardiovascular risk factors (Hcy and PRC) in patients with GABS. Methods: The research was conducted experimentally under laboratory conditions and was applied in nature, utilizing a cross-sectional research design. The research plan included random allocation to four groups: aerobic exercise, aerobic exercise + curcumin, curcumin, and control group. The aerobic exercise group and the aerobic exercise + curcumin group participated in a structured exercise program focused on rehabilitation exercises, while the curcumin group received the supplement, and the control group received no intervention. Results: The results indicated that the VO2max values were significantly different between the aerobic exercise + curcumin group and both the curcumin and placebo groups, as well as between the curcumin group and the placebo group. Additionally, serum Hcy levels were significantly different between the aerobic exercise and placebo groups and between the aerobic exercise + curcumin and placebo groups. Furthermore, the serum PRC levels were significantly different between the aerobic exercise and placebo groups and between the aerobic exercise + curcumin and placebo groups. Conclusion: Therefore, it can be concluded that the use of rehabilitation exercises along with curcumin consumption is recommended for improving aerobic capacity and reducing cardiovascular risk factors in patients with GABS.